EFEKTIVITAS SISTEM INFORMASI MANAJEMEN SI D’nOK (SISTEM INFORMASI DOKU INFORMASI DOKUMEN ONLINE KEPENDUDUKAN) DALAM PELAYANANMEN ONLINE KEPENDUDUKAN) DALAM PELAYANAN - Mushaffa Faiz Akmal; Ida Hayu Dwimawanti; Tri Yuniningsih (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
Technology that is experiencing rapid development must be utilized in various fields to facilitate activities, including government services. Technological progress has been utilized by the Semarang City Population and Civil Registry Service by bringing out innovations in population document services through SI D'nOK (Population Online Document Information System), one of which includes managing birth certificate documents. However, in the course of this application there are still some problems that are felt by the community when using the application. Therefore, it is necessary to analyze further related to the effectiveness of the information system. In this study using qualitative research methods with a descriptive approach. This study uses Delone and McLean's theory to answer research problems related to Information System Effectiveness and uses Argo Pambudi's theory to analyze related inhibiting factors. The research results show that the SI D'nOK Information System has not been effective and the main inhibiting factors are community culture and socialization which are still lacking. The recommendations that can be given by researchers are the Semarang City Disdukcapil in managing the Population Online Document Information System, namely increasing socialization that can reach all groups and improving applications to prevent problem when using them.